TRODAT SPECT in patients with idiopathic REM sleep behaviour disorder - Geraldo Nunes Vieira Rizzo (Sleep Science)
Objective: to determine the value of dopamine transporter (DAT) neuroimaging radiotracer in a group of idiopathic rapid eye movement sleep behavior disorder (iRBD) patients regarding the development of a synucleinopathy. Methods: 6 retrospectively selected patients with clinical and polysomnographic diagnosis of iRBD, on treatment or not, were submitted to a single-photon emission computerized tomography (SPECT) with TRODAT. Results: Five from six patients have an abnormal test showing reduction in DAT density measured by the linkage potential on SPECT. Conclusions: TRODAT crosses the blood brain barrier, has a high affinity for DAT and is capture by SPECT. The decreased uptake of DAT tracers means a reduction in dopaminergic activity which suggest the possibility of Parkinson Disease. We have tried to reinforce iRBD as a marker of neurodegenerative disease and suggest SPECT with TRODAT as an easy method in our country to follow longitudinally these patients.